Mental states and temperaments contributing to suicidal crisis in psychiatric inpatients: a cross-sectional and validation study - Marco Innamorati; Denise Erbuto; Elena Rogante; Salvatore Sarubbi; Maria Anna Trocchia; Mariarosaria Cifrodelli; Monica Migliorati; Anna Comparelli; Isabella Berardelli; Maurizio Pompili (BMC Psychiatry)
Abstract Background A suicide crisis represents a psychological state preceding a suicide behavior and occurs when an individual experiences intolerable emotions. Only a few instruments have been developed so far to assess cognitions and emotions associated with a specific interpretative model of the suicide crisis. Objectives We aimed to (1) evaluate the psychometric properties of a new questionnaire (Suicidal Crisis Evaluation Scale, SCES) that could potentially assess cognitions and emotions relevant to the suicide crisis; (2) evaluate whether cognitions and emotions investigated with the SCES were characteristics of psychiatric patients at greater risk for suicide; (3) investigate whether the presence and severity of suicide-relevant cognitions and mental states could be associated with affective temperaments; and (3) study whether the severity of current depression at least partially mediated the association between affective temperaments and negative mental states. Methods We included 188 adult psychiatric inpatients admitted to the Sant’Andrea Hospital psychiatric inpatient unit in Rome. We administered the SCES and questionnaires to measure current depression, and affective temperaments. Results A common factor explained around 70% of SCES variance, and SCES scores were significantly higher in patients with a recent suicide attempt than in other patients. Part of the variance in common between some affective temperaments and SCES scores was explained by the presence and severity of current depressive symptoms. Conclusion Psychiatric patients need to be assessed for the presence and severity of cognitions and emotions present during the suicide crisis for a better understanding of the complex architecture of suicide risk. The SCES is a valid and reliable measure that could capture such mental states. More studies are necessary to confirm and expand our results in independent samples.